Jesus der Täufer und die Reinwaschung der Jünger - Förster, Niclas (New Testament studies, 2018)
The dispute about purification' between the disciples of John the Baptist and a Jew (John 3.25) has to do with the priority of ethical purity as effected through baptism over the ritual washing prescribed by the Torah, e.g. before entering the Jerusalem temple. This issue is referred to in John 13.10 and 15.3, and also in P.Oxy. 840. It is presupposed here that the circle of Jesus' disciples received John's baptism of repentance either from John the Baptist or from Jesus (John 3.22, 26; 4.1). The Gospel of John thus engages with an ongoing debate within Jewish Christianity about the obligatory nature of ritual washing.